FEELING THE COLD: ATMOSPHERIC CO2 ENRICHMENT AND THE FROST SENSITIVITY OF TERRESTRIAL PLANT FOLIAGE - Beerling D.J.; Terry A.C.; Hopwood C.; Osborne C.P. (My University, 2002)
Quantitative palaeoclimate reconstructions from plant fossils using the nearest living relative (NLR) approach axiomatically assume that the climatic limits of plant distributions have largely remained unchanged over at least the past 250 Myr. However, throughout much of the Mesozoic the atmospheric CO2 concentration is predicted to have been several times greater than the present day, and long-term (=<5 yr) experimental co2 enrichment studies indicate this has the capacity to increase the frost sensitivity of plant foliage by raising the temperature at which leaf tissues freeze. Furthermore, we have been able to document increases in the leaf freezing temperatures of some woody shrub species in response to the rise in atmospheric CO2 concentration over the past two centuries, suggesting leaf freezing temperatures are sensitive to below ambient CO2 concentrations. These data imply that a previously unrealised increase in the frost sensitivity of terrestrial plants may have already occurred owing to anthropogenic impacts on the contemporary global carbon cycle. Possible consequences of these findings for palaeotemperatures generated from the application of the NLR technique to a time-series of floras are discussed, with particular attention given to differential effects resulting from the nature of the leaf freezing-CO2 relationship.
Keywords: ATMOSPHERIC CO2; ICE NUCLEATION TEMPERATURE; NEAREST LIVING RELATIVE; PALAEOCLIMATE; TERRESTRIAL VEGETATION; Mesozoic; Mesozoic; Мезозой